Individual Field Project: Applying Theoretical Know-how to Real-life Business and Engineering Situation - Lee, Khai Loon (Penerbit UMP, 2021)
This book intended to share the findings obtained from Individual Field Project. It is one of the courses for Bachelor of Business Engineering with Honours, Universiti Malaysia Pahang. All projects are either suggested by the authors or advised by a company. The chapters demonstrated the possibility to apply theoretical concepts and tools in a practical setting. Therefore, the authors required occasional presence in a company to study and investigate the real industrial case. It is to enable the authors to apply theoretical know-how to real-life business and engineering situations. All projects have been reviewed and proofread by the respective academic supervisor, and only the selected paper and the paper that received consensus from the company will be published in this book.